Demineralization Inhibition by High‐Speed Scanning of 9.3 µm CO2 Single Laser Pulses Over Enamel. Issue 5 (8th November 2020) - Badreddine, Ali H.; Couitt, Stephen; Donovan, Julia; Cantor‐Balan, Roni; Kerbage, Charles; Rechmann, Peter
Abstract : Background and Objective: In vitro studies were conducted to evaluate the use of an automated system for high‐speed scanning of single 9.3 µm CO2 laser pulses in the inhibition of caries‐like lesion formation in the enamel of extracted human molars. The effect of the laser in generating an acid‐resistant layer and the effect of the layer on inhibiting surface mineral loss during pH cycling was explored. Study Design/Materials and Methods: Laser irradiation was performed with fluences of 0.6, 0.8, and 1.0 J/cm 2 for single pulses of 1 mm diameter (1/e 2 ), with pulse durations of 17, 22, and 27 microseconds, respectively. The laser was scanned at a 750 Hz pulse repetition rate in an automated pattern covering an area of 7 mm 2 in 0.3 sec. Six treatment groups were investigated: three groups for each fluence for laser‐only and three for laser irradiation with additional fluoride from a toothpaste slurry (sodium fluoride at 1100 ppm). Each group used non‐irradiated areas, which included untreated controls for the laser‐only groups and a fluoride‐only treatment for the groups with additional fluoride. pH cycling was performed on both groups, followed by microhardness testing to determine the relative mineral loss (∆ Z ) from a caries‐like formation and surface mineral loss (∆ S ). Results: Laser irradiation with the 9.3 µm CO2 laser generated an acid‐resistant layer of about 15 µm in depth. For the laser‐irradiated samples with additional fluoride application, the relative mineral loss (∆Z) was 113 ± 63 vol%‐µm, while for those with only fluoride application ∆Z was 572 ± 172 vol%‐µm. At the highest fluence (1.0 J/cm 2 ) used, an 80.2% inhibition of caries‐like lesion was measured by ∆Z. Using only laser irradiation at the highest fluence resulted in an inhibition of caries‐like lesion of 79.5% for the irradiated samples (∆Z = 374 ± 149 vol%‐µm) relative to the control (∆Z = 1826 ± 325 vol%‐µm). Surface microhardness tests resulted in an inhibition of surface softening, as measured by the Knoop Hardness Value (KHN) (108 ± 33 KHN for laser irradiated with additional fluoride, for non‐irradiated controls with fluoride only 52 ± 16 KHN). Inhibition of surface loss was observed for all laser fluences, but the maximum surface loss for the untreated control group was only 2.2 ± 0.49 µm. Conclusions: The results demonstrate a significant benefit of the 9.3 µm CO2 laser at fluences of 0.6, 0.8, and 1.0 J/cm 2 in caries‐like lesion inhibition as measured by the relative mineral loss in depth and surface mineral loss, without significant damage to the enamel. Additionally, inhibition of surface softening and surface loss during pH cycling was observed. The surface loss was small compared with the overall lesion depth and thickness of the generated acid‐resistant layer. Lasers Surg. Med. © 2020 Wiley Periodicals LLC